Portal hypertension in patients with cirrhosis: indirect assessment of hepatic venous pressure gradient by measuring azygos flow with 2D-cine phase-contrast magnetic resonance imaging. - Gouya, Hervé; Grabar, Sophie; Vignaux, Olivier; Saade, Anastasia; Pol, Stanislas; Legmann, Paul; Sogni, Philippe; Gouya, Hervé (European Radiology, 2016)
Objectives: To measure azygos, portal and aortic flow by two-dimensional cine phase-contrast magnetic resonance imaging (2D-cine PC MRI), and to compare the MRI values to hepatic venous pressure gradient (HVPG) measurements, in patients with cirrhosis.Methods: Sixty-nine patients with cirrhosis were prospectively included. All patients underwent HVPG measurements, upper gastrointestinal endoscopy and 2D-cine PC MRI measurements of azygos, portal and aortic blood flow. Univariate and multivariate regression analyses were used to evaluate the correlation between the blood flow and HVPG. The performance of 2D-cine PC MRI to diagnose severe portal hypertension (HVPG ≥ 16 mmHg) was determined by receiver operating characteristic curve (ROC) analysis, and area under the curves (AUC) were compared.Results: Azygos and aortic flow values were associated with HVPG in univariate linear regression model. Azygos flow (p < 10(-3)), aortic flow (p = 0.001), age (p = 0.001) and presence of varices (p < 10(-3)) were independently associated with HVPG. Azygos flow (AUC = 0.96 (95 % CI [0.91-1.00]) had significantly higher AUC than aortic (AUC = 0.64 (95 % CI [0.51-0.77]) or portal blood flow (AUC = 0.40 (95 % CI [0.25-0.54]).Conclusions: 2D-cine PC MRI is a promising technique to evaluate significant portal hypertension in patients with cirrhosis.Key Points: • Noninvasive HVPG assessment can be performed with MRI azygos flow. • Azygos MRI flow is an easy-to-measure marker to detect significant portal hypertension. • MRI flow is more specific that varice grade to detect portal hypertension.